2012
DOI: 10.1021/jm2014666
|View full text |Cite
|
Sign up to set email alerts
|

Novel cGMP Efflux Inhibitors Identified by Virtual Ligand Screening (VLS) and Confirmed by Experimental Studies

Abstract: Elevated intracellular levels of cyclic guanosine monophosphate (cGMP) may induce apoptosis, and at least some cancer cells seem to escape this effect by increased efflux of cGMP, as clinical studies have shown that extracellular cGMP levels are elevated in various types of cancer. The human ATP binding cassette (ABC) transporter ABCC5 transports cGMP out of cells, and inhibition of ABCC5 may have cytotoxic effects. Sildenafil inhibits cGMP efflux by binding to ABCC5, and in order to search for potential novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…For example, zebrafish, mouse and human ABCC5 are more closely related to one another than to other ABCC family members from the same organism (Korolnek et al, 2014), suggesting potential conservation of function. Consistent with this idea, Hs-ABCC5 has similar topology (Ravna et al, 2008;Sager et al, 2012), subcellular localization (Borst et al, 2007;Korolnek et al, 2014;Meyer Zu Schwabedissen et al, 2005;Wijnholds et al, 2000), and fluorescent substrates to sea urchin C5a. For instance, McAleer et al (1999), showed that Hs-ABCC5 strongly effluxes FDA and CMFDA, but does not efflux C-AM or rhodamine dyes.…”
Section: Evolutionary Implications Of C5a-mediated Gut Morphogenesissupporting
confidence: 55%
See 1 more Smart Citation
“…For example, zebrafish, mouse and human ABCC5 are more closely related to one another than to other ABCC family members from the same organism (Korolnek et al, 2014), suggesting potential conservation of function. Consistent with this idea, Hs-ABCC5 has similar topology (Ravna et al, 2008;Sager et al, 2012), subcellular localization (Borst et al, 2007;Korolnek et al, 2014;Meyer Zu Schwabedissen et al, 2005;Wijnholds et al, 2000), and fluorescent substrates to sea urchin C5a. For instance, McAleer et al (1999), showed that Hs-ABCC5 strongly effluxes FDA and CMFDA, but does not efflux C-AM or rhodamine dyes.…”
Section: Evolutionary Implications Of C5a-mediated Gut Morphogenesissupporting
confidence: 55%
“…A number of studies have shown that mammalian ABCC5 transports cyclic nucleotides (Boadu and Sager, 2004;Jedlitschky et al, 2000;Meyer Zu Schwabedissen et al, 2005;Sager and Ravna, 2009;Sager et al, 2012;Wielinga et al, 2003;Wijnholds et al, 2000). cGMP is reported to be a higher-affinity substrate than cAMP, but the exact affinity of cGMP remains unclear Pratt et al, 2005;Reid et al, 2003;Wielinga et al, 2003).…”
Section: Substrates Of C5amentioning
confidence: 99%
“…Table 3 reports the binding site score for the ABCC5 model and lists the residues composing the site. Predicted active site residues like ASN 441, GLN 1138 were consistent with ABCC5 model [9].…”
Section: Resultssupporting
confidence: 58%
“…Different models of ABCC5 [9] [10] are previously presented in outward-facing conformations and inward-facing conformations based on the Staphyllococcus aureus ABC transporter Sav1866 [11], which has been crystallized in an outward-facing ATP-bound state, and on the Escherichia coli MsbA, which has been crystallized in a wide open inward-facing conformation [12]. In this study, multiple homology models of ABCC5 are constructed on the X-ray crystal structure of five different ABC transporters (PDB IDs: 4F4C, 4Q9H, 4M1M, 4M2T and 4KSD) and all models are ranked as per their structural quality.…”
Section: Introductionmentioning
confidence: 99%
“…LBVS explores biological data to identify known active or inactive compounds form biological data to retrieve other potentially active molecular scaffolds based on similarity measures such as common descriptor values. A combination of these two approaches has also been proposed previously [42]. Recently, SBVS has been proven to be more effective than the other traditional ways of drug discovery [30].…”
Section: Vs (Sbvs) and Ligand-based Vs (Lbvs)mentioning
confidence: 99%